Analisis Faktor-Faktor yang Mempengaruhi Nilai Perusahaan - Vivi Indah Bintari; Deasy Lestary Kusnandar (Jurnal Bisnis dan Ekonomi, 2020)
..................... The objective of this research is to investigate the effect of profitability, liquidity, leverage, dividend policy and firm size to firm value of Jakarta Islamic Index (JII) in 2015-2019. The population in this study consisted of 30 companies belonging to the Jakarta Islamic Index with a 5- year research period. The sampling method used in this research is purposive sampling and the results are 6 companies according to the criteria of the sample. Pooling data method is used to collect the data and ordinary least squares (OLS) as the analysis method. The results showed that partially profitability had no significant effect on firm value, liquidity had no significant effect on firm value, leverage had no significant effect on firm value, dividend policy had significant effect on firm value, firm size had significant effect on firm value. Simultaneously shows that the profitability, liquidity, leverage, dividend policy and firm size have a simultaneous effect on firm value.